Games for experiential learning: Triggering collective changes in commons management - Falk, Thomas; Zhang, Wei; Meinzen-Dick, Ruth S.; Bartels, Lara; Sanil, Richu; Priyadarshini, Pratiti; Soliev, Ilkhom (Resilience Alliance, Inc., 2023)
As resource users interact and impose externalities onto each other, institutions are needed to coordinate resource use, create trust, and provide incentives for sustainable management. Coordinated collective action can play a key role in enabling communities to manage natural resource commons more sustainably. But when such collective action is not present, what can be done to foster it? We contribute to the understanding of how experiential learning through games can affect behavioral change, potentially leading to more sustainable commons management. We present a conceptual framework describing the most important processes involved in experiential learning games. The framework highlights the importance of the game context for achieving game outcomes. We list game features that have been argued to influence learning and behavioral determinants, focusing on the game narrative and experience, game rules, and attributes of players. We briefly describe how each game feature influences the processes in the framework. Next, we apply the conceptual framework to examine design features that were particularly important for influencing behavioral drivers in commons management in three intervention cases from India relating to groundwater, surface water, and forests. Our conceptual reflections underpin the need to debate about underlying assumptions in using games as intervention tools. Making assumptions transparent can help to understand why or under what conditions experiential learning works or fails. There is a critical need for more systematic choices of the right tools for the right purpose. This includes participants of the experiential learning who must be able to relate the game to their real life. A social dilemma in the game should at least, in its basic structure, represent a real-life dilemma. We close by highlighting future research needs both from the conceptual behavioral change as well as the game design perspective.